2008
DOI: 10.1111/j.1469-8986.2008.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 28 hours of sleep deprivation on respiratory sinus arrhythmia during tasks with low and high controlled attention demands

Abstract: Task performance while sleep deprived may be moderated by the controlled attention required by the task (Pilcher, Band, Odle-Dusseau, & Muth, 2007). This study examined the effects of 28 h of sleep deprivation on respiratory sinus arrhythmia (RSA) during tasks with low and high controlled attention demands. The results showed that RSA increased throughout the night for both task types, but was consistently reduced during the low compared to high controlled attention tasks. The increase in RSA was linear for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 40 publications
(65 reference statements)
1
12
0
Order By: Relevance
“…Our view is also in line with the recent finding of significant functional connectivity between right anterior insula and ACC across different attention-demanding tasks, leading to the conclusion that the right anterior insula may be especially critical for modulating cognitive control systems under challenging conditions [Eckert et al, 2009]. Apart from cognitive challenges, this might also, or even particularly, apply to very simple tasks like ours, which are challenging, because they are repetitive and ultimately boring but still require the continuous, effortful maintenance of attention [Fischer et al, 2008;Langner et al, 2010b;Walker et al, 2009].…”
Section: Arousal Regulation and The Implementation Of Task Setssupporting
confidence: 67%
“…Our view is also in line with the recent finding of significant functional connectivity between right anterior insula and ACC across different attention-demanding tasks, leading to the conclusion that the right anterior insula may be especially critical for modulating cognitive control systems under challenging conditions [Eckert et al, 2009]. Apart from cognitive challenges, this might also, or even particularly, apply to very simple tasks like ours, which are challenging, because they are repetitive and ultimately boring but still require the continuous, effortful maintenance of attention [Fischer et al, 2008;Langner et al, 2010b;Walker et al, 2009].…”
Section: Arousal Regulation and The Implementation Of Task Setssupporting
confidence: 67%
“…Several studies have shown that tasks that have a long duration and a large amount of controlled attention (i.e. vigilance tasks) can cause different patterns in RSA than tasks with short duration and a low amount of controlled attention (Althaus et al, 1998;Walker et al, 2009). It is possible that the large amount of variance was due to the different nature of the cardinal direction task when compared to the other 6 tasks.…”
Section: Discussionmentioning
confidence: 95%
“…Fishel et al (2006) monitored changes in RSA during a dual task paradigm with high task load and low task load conditions, and found that for tasks lasting longer than 2 min, RSA was significantly lower in the high task load condition than the low task load condition. In a study investigating patterns in RSA while performing tasks of varying task load during sleep deprivation, Walker et al (2009) found that RSA was significantly lower in tasks with a high cognitive demand than in tasks with a low cognitive demand. In another study comparing the sensitivity of the different bands of HRV, Althaus et al (1998) found that, when controlling for respiration, only the RSA frequency of HRV was sensitive to changes in task load.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, the lack of sleep and sleep deprivation are associated with negative changes in mood, increased irritability, and emotional instability (Horne, 1985;Wong, et al, 2013) as well as physiological changes associated with a stress response (McCubbin, Pilcher, & Moore, 2010;Walker, et al, 2009). Sleep deprivation increases negative mood states (Durmer & Dinges, 2005), worsens emotional regulation (Baum, et al, 2014), and induces extra sensitivity to emotional and stressful events (Vandekerckhove & Cluydts, 2010).…”
Section: Introductionmentioning
confidence: 88%